The Romberg sign, unilateral vestibulopathy, cerebrovascular risk factors, and long-term mortality in dizzy patients - Berge, Jan Erik; Goplen, Frederik Kragerud; Aarstad, Hans Jørgen; Storhaug, Tobias Andre; Nordahl, Stein Helge Glad (Frontiers in Neurology, 2022)
Objectives Describe the relationship between unsteadiness, canal paresis, cerebrovascular risk factors, and long-term mortality in patients examined for dizziness of suspected vestibular origin. Study design Observational cohort with prospective collection of survival data. Setting University clinic neurotological unit. Patients Consecutive patients aged 18–75 years examined in the period 1992–2004 for dizziness of suspected vestibular origin. Outcome measures Overall survival. Standardized mortality ratio (SMR). Factors: Unsteadiness, canal paresis, age, sex, patient-reported diabetes, hypertension, heart disease, stroke, or TIA/minor stroke. Patients were classified as steady or unsteady based on static posturography at baseline compared to normative values. Results The study included 1,561 patients with mean age 48 years and 60 % females. Mean follow-up was 22 years. Unsteadiness was associated with higher age, heart disease, diabetes, hypertension, and cerebrovascular dizziness. There were 336 deaths over 31,335 person-years (SMR 0.96; 95 % confidence interval: 0.86–1.07). Canal paresis was not related to unsteadiness (chi square: p = 0.46) or to mortality (unadjusted Cox hazard ratio: 1.04, 95% CI: 0.80–1.34). Unsteadiness was an independent predictor of mortality (adjusted Cox hazard ratio: 1.44, 95% CI: 1.14–1.82). Conclusions Unsteadiness measured by static posturography is associated with higher age, known cerebrovascular risk factors, and with increased long-term mortality, but not with canal paresis in patients evaluated for dizziness. The study highlights the importance of evaluating patients with conspicuous postural instability for non-vestibular causes.